The Effect of Interactive Multimedia-Based Discovery Learning on Students' Ability to Understand Mathematical Concepts - Wulandari, Nur Rahmah; Tasriyah (International Journal of Research in Mathematics Education, 2024)
This research was conducted based on the low ability to understand mathematical concepts of class VII students at MTs Al-Masruriyyah Baturraden. Researchers chose an interactive multimedia-based discovery learning learning model to address students' ability to understand mathematical concepts. The aim of this research was to find out how it was implemented and whether there was an influence of interactive multimedia-based discovery learning on students' ability to understand mathematical concepts. The type of research used is quantitative research using experimental methods. The population of this research was all class VII, totaling 60 students, with a sample of 19 students in class VII A, and 21 students in class VII C. Data collection methods were carried out by observation and tests. Data analysis techniques use normality tests, homogeneity tests, and t tests. Based on the results of the t test on the post test, a value of 0.001 < 0.05 was obtained, so H_1 was accepted. So it can be concluded that there is an influence between the interactive multimedia-based discovery learning model on the ability to understand mathematical concepts. Keywords: Discovery Learning, Interactive Multimedia, Understand Mathematical Concepts.